2004
DOI: 10.21168/rbrh.v9n4.p21-31
|View full text |Cite
|
Sign up to set email alerts
|

Uma Análise na Dragagem do Complexo Estuarino-Lagunar Mundaú/Manguaba em Alagoas através de um Modelo Numérico Hidrodinâmico Bidimensional ? Resultados Preliminares

Abstract: O presente trabalho faz parte dos estudos inseridos no plano de ações e gestão integrada para o Complexo Estuarino-Lagunar Mundaú/ Manguaba (CELMM), localizado a sudeste da cidade de Maceió no Estado de Alagoas, imprescindível para o desenvolvimento de um programa estratégico de intervenção na região de abrangência do CELMM, com a definição de medidas estruturais e não-estruturais e do arranjo institucional necessário para que as ações possam ser efetivamente implementadas. Este trabalho tem o objetivo de anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…• Analyze the characteristic hydraulic times (CHT), considering the concepts of Residence Time (RT) and Water Age (WA), in different sectors of the lagoon system. This study deepens aspects of similar studies, relevant to the MMELS, among them: Larsson and Nilsson (2014); Lima (2017); Souza (2017) ;Brito Jr. et al (2018); Cunha et al (2021) and Pinheiro et al (2021). Most of the cited works discuss the RT.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…• Analyze the characteristic hydraulic times (CHT), considering the concepts of Residence Time (RT) and Water Age (WA), in different sectors of the lagoon system. This study deepens aspects of similar studies, relevant to the MMELS, among them: Larsson and Nilsson (2014); Lima (2017); Souza (2017) ;Brito Jr. et al (2018); Cunha et al (2021) and Pinheiro et al (2021). Most of the cited works discuss the RT.…”
Section: Introductionsupporting
confidence: 82%
“…In the Mundaú L, the residual currents became a large-scale, counterclockwise circular movement. Authors such as ANA (2013), Souza (2017) and Brito Jr. et al (2018) also observed such a pattern, which influences the scattering of constituents present on each margin. The circulatory cell located in front of Silva's Stream stands out.…”
Section: Hydrodynamics Analysismentioning
confidence: 88%
“…In their analysis, they concluded that in Mundaú Lagoon currents and mixing are dominated by tides and modified by freshwater discharge, while in Manguaba Lagoon, tides are very small and wind force becomes dominant. Souza et al (2004) developed a bi-dimensional hydrodynamic circulation model of the exchanges between oceanand lagoon-complex waters due to the bathymetric change in the channel. De Lima (2017) used bi-dimensional modeling and Mike 21 software to calculate the residence time of a pollutant, exemplified by a tracer inserted in the two lagoons.…”
Section: Figure 1 Mundaú-manguaba Lagoon Estuary Complex (Celmm) Inmentioning
confidence: 99%
“…It pattern was corroborated by Hepp & Santos (2009), who affirm that anthropic changes in watersheds cause geological and chemical alterations in the water body that reach the associated biota. In MMELC, several changes in the landscape are evident which, according to Souza et al (2004), alter the ecological balance, causing environmental disturbances such as reduction in species richness. In the interpretation of results, it is clear that environments with riparian vegetation cover (forest or grasses) have greater species richness and environments with influence of urban effluents have high P. reticulata percentage.…”
Section: Discussionmentioning
confidence: 99%